A Survey of Cloud Computing Service and Security issues (International Journal of Engineering and Computer Science, 2014)
This paper is the survey and concept of Cloud Computing Establishment and security issues. Cloud Computing is considered as one of the emerging arenas of computer science in recent times. It is providing excellent facilities to business entrepreneurs by flexible infrastructure. Although, cloud computing is facilitating the Information Technology industry, the research and development in this arena is yet to be satisfactory. Our contribution in this paper is an advanced survey focusing on cloud computing concept and most Security issues